(untitled) (Journal of Parents and Teachers, 2014)
Self-esteem is the image we have of our own worth and is based on experiences, thoughts and feelings. Taking advantage of the school year, it is possible to try to improve behaviours whose origin lies in "low self-esteem". Some behaviours that both parents and teachers should avoid are calling them bad/clumsy, not positively reinforcing good behaviour, undervaluing ourselves so that we offer them a poor role model, biting criticism when they make a mistake, etc.